Obesity, Diet, and Activity in relation to Asthma and Wheeze among Rural Dwelling Children and Adolescents - Joshua A. Lawson; Donna C. Rennie; James A. Dosman; Allison L. Cammer; Ambikaipakan Senthilselvan (Hindawi Limited, 2013)
Aims and Objectives. We investigated associations between weight status, activity level, and diet with asthma or wheeze as well as the interrelationship between these factors. Methods. We conducted a case-control study of 6-18-year olds from 2005 to 2007. Cases () were subjects reporting episodes or breathing medication use along with doctor-diagnosed asthma or wheeze in the past 12 months. Controls were randomly selected () and without asthma or wheeze. Data regarding health outcomes, diet, and activity were obtained from questionnaire. Objectively measured height and weight were collected. Results. In the adjusted analysis, there was a trend () towards an increased risk of asthma or wheeze associated with high fast food and/or pop consumption. Among cases, a significantly lower proportion (66%) classified as overweight participated in hard exercise in ≥9 of the past 14 days compared to those who were not overweight (86%). This pattern was not seen among controls (76% participating in hard exercise versus 78%, resp.). However, based on perceived weight status by the parent, the patterns were similar regardless of case-control status. Conclusions. Overweight status may negatively impact activity level among those with asthma or wheeze. Efforts should be made to encourage healthy food choices, and activity programming must consider the needs of overweight children with asthma.